وسط الحفظ بالمتحف الوطني للأثار بسطيف - مياطه, التجاني (جامعة الوادي - University of Eloued, 2013)
The importance of conservation and protection within our museums of topics and issues important to preserve the historical and cultural heritage from extinction and damage, and in this regard was the subject of our study which deals with the National Museum of Antiquities Setif An Empirical Study of the central conservation. The seriousness of the subject lies in highlighting the negative and positive aspects, views, storage and conservation center of the current museum and the means and methods used to maintain the holdings of external influences, both human and biological also climatic. The study includes the solutions and suggestions in order to provide a lasting climate to maintain the museum's holdings of all effects, in addition to providing the means for the prevention of all workers from the ravages and furniture appropriate in line with the functions of the display, storage and commensurate with the museum's holdings
مقال
Keywords: الارث الحضاري.المتحف.الآثار.سطيف.الجزائر.وسائل الخفظ